2013
DOI: 10.1371/journal.pone.0067668
|View full text |Cite
|
Sign up to set email alerts
|

The EphB4 Receptor Tyrosine Kinase Promotes Lung Cancer Growth: A Potential Novel Therapeutic Target

Abstract: Despite progress in locoregional and systemic therapies, patient survival from lung cancer remains a challenge. Receptor tyrosine kinases are frequently implicated in lung cancer pathogenesis, and some tyrosine kinase inhibition strategies have been effective clinically. The EphB4 receptor tyrosine kinase has recently emerged as a potential target in several other cancers. We sought to systematically study the role of EphB4 in lung cancer. Here, we demonstrate that EphB4 is overexpressed 3-fold in lung tumors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
52
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 61 publications
2
52
0
Order By: Relevance
“…Our laboratory has recently shown that KSR1 also promotes anchorageindependent growth and tumor maintenance in human colon tumor cell lines (16 (16,19,44,45), the similarity of siKSR1-and siEPHB4-dependent gene expression signatures suggests that EPHB4 is likely to support colon tumor cell survival similarly to KSR1. EPHB4 expression is elevated in a variety of human cancers, including cancers of the head and neck, prostate, bladder, ovaries, large intestine, lung, brain, pancreas, and esophagus (46)(47)(48)(49)(50)(51)(52)(53)(54). We analyzed the expression of EPHB4 in a panel of colon tumor cells compared to its expression in HCECs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our laboratory has recently shown that KSR1 also promotes anchorageindependent growth and tumor maintenance in human colon tumor cell lines (16 (16,19,44,45), the similarity of siKSR1-and siEPHB4-dependent gene expression signatures suggests that EPHB4 is likely to support colon tumor cell survival similarly to KSR1. EPHB4 expression is elevated in a variety of human cancers, including cancers of the head and neck, prostate, bladder, ovaries, large intestine, lung, brain, pancreas, and esophagus (46)(47)(48)(49)(50)(51)(52)(53)(54). We analyzed the expression of EPHB4 in a panel of colon tumor cells compared to its expression in HCECs.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanistic role that EPHB4 plays in cancer remains controversial. However, a preponderance of data indicate that EPHB4 is overexpressed broadly in human cancers, including cancers of the head and neck, prostate, bladder, ovaries, large intestine, lung, brain, pancreas, and esophagus (46)(47)(48)(49)(50)(51)(52)(53)(54). Further research has shown that the ablation or inhibition of EPHB4 in a number of cancer cell types reduces tumor cell viability, including prostate (47), bladder (48), ovarian (49), colon (50), lung (51), head and neck squamous cell carcinoma (74), and esophageal (54) cancer.…”
Section: Discussionmentioning
confidence: 99%
“…(77,81) The Eph receptors/ephrins have also been implicated in tumourigenesis, progression and metastasis across a wide range of malignancies (Table 3). ( (83) Prostate cancer (84,85) Breast cancer (86,87) Melanoma (88) Glioblastoma (89,90) Gastric cancer (91) EphA3 Gastric cancer (92) Colorectal cancer (93) EphB2 Advanced cSCC (94) Glioblastoma (95)(96)(97) Cervical cancer (98) Breast cancer (99) EphB4 HNSCC (100) Non-small cell lung cancer (101) Breast cancer (99) Downregulated EphA1 NMSC (77) …”
Section: Galaninmentioning
confidence: 99%
“…The sole, physiologically relevant ligand for EphB4 is ephrin-B2, a transmembrane protein expressed on the surface of certain cells, which interacts with EphB4 on adjacent cells during cell-to-cell contact. Data supports a role for EphB4-ephrin-B2 interaction in tumour angiogenesis and suggests that EphB4 positive tumour cells may preferentially attach to ephrin-B2 expressing endothelial cells during extravasation which is the process of translocation of circulating tumour cells out of blood vessels into surrounding tissues, thereby promoting metastatic spread [14][15][16][17][18][19].…”
mentioning
confidence: 90%
“…EphB4 is a protein receptor expressed in increased amounts on the surface of cancer cells, including those from the prostate, and its function has been linked to several processes important for metastatic spread, including cell viability, migration, invasion and adhesion [14][15][16][17][18][19]. The sole, physiologically relevant ligand for EphB4 is ephrin-B2, a transmembrane protein expressed on the surface of certain cells, which interacts with EphB4 on adjacent cells during cell-to-cell contact.…”
mentioning
confidence: 99%